A multidimensional physical therapy program for individuals with cerebellar ataxia secondary to traumatic brain injury: a case series. (February 2014) - Sartor-Glittenberg, Cecelia; Brickner, Lori
Abstract The purpose of this case series is to describe changes in impairments and activity limitations in three individuals with severe cerebellar ataxia from traumatic brain injury (TBI) who participated in a long-term, multidimensional physical therapy program. A secondary purpose is to document use of a climbing wall for these persons. Each of the individuals had a TBI, severe ataxia and was admitted to a transitional neuro-rehabilitation day treatment program. The first person, a 22-year-old, was 6 years post injury and had 127 individual physical therapy sessions over 12 months. The second person, a 16-year-old, was 5½ months post injury and had 187 individual therapy sessions over 19 months. The third person, a 20-year-old, was 6 months post injury and had 89 individual therapy sessions over 23 months. An integrative treatment approach was used, and the individuals participated in activities to minimize ataxia and improve mobility. Each of them made gains in coordination, balance, balance confidence, endurance and mobility. The three individuals with cerebellar ataxia participated in a long-term, individualized, multidimensional physical therapy treatment program, and made improvements in all areas of impairment and activity limitations. This study reinforces the need for long-term, multidimensional physical therapy for individuals with ataxia.